2022
DOI: 10.1108/ijoes-05-2022-0091
|View full text |Cite
|
Sign up to set email alerts
|

Muzakki and Mustahik’s collaboration model for strengthening the fundraising capacity of Islamic social finance institutions during COVID-19

Abstract: Purpose This study aims to examine how muzakki (zakat donator) and mustahik (zakat recipients) collaborated to strengthen the fundraising capability in Islamic social finance institutions (ISFIs) during the COVID-19. Design/methodology/approach This study uses a descriptive qualitative method in conjunction with interview techniques. Interviews with muzakki of various professions were conducted, as well as data from field documentation, to develop a collaborative model of muzakki and mustahik in strengthenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…During covid-19, the role of zakat is very large, proven in various countries zakat helps the community not only in Indonesia (Ascarya, 2021;Fithor et al, 2021) but also other countries such as in Malaysia (Zahri et al, 2023) and Nigeria (Umar & Danlami, 2022). Another thing that needs to be done in an effort to increase zakat participation is collaboration between mustahik and muzzaki (Herianingrum et al, 2022). Nowadays, financial technology even plays an important role in zakat collection activities (Shaikh, 2020).…”
Section: Cross Tabulation Analysis Resultsmentioning
confidence: 99%
“…During covid-19, the role of zakat is very large, proven in various countries zakat helps the community not only in Indonesia (Ascarya, 2021;Fithor et al, 2021) but also other countries such as in Malaysia (Zahri et al, 2023) and Nigeria (Umar & Danlami, 2022). Another thing that needs to be done in an effort to increase zakat participation is collaboration between mustahik and muzzaki (Herianingrum et al, 2022). Nowadays, financial technology even plays an important role in zakat collection activities (Shaikh, 2020).…”
Section: Cross Tabulation Analysis Resultsmentioning
confidence: 99%
“…As evidence of collaborative endeavors in producing joint studies, Although 811 authors were considered in this study, Figure 10 shows only authors with at least two studies published and one cited. Finance (Hassan et al, 2021a;Hassan et al, 2021b;Herianingrum et al, 2022), the sustainability index , the nexus between Islamic social finance, human resources, governance, and poverty (Widiastuti, Prasetyo, et al, 2022), integration of sustainability in Islamic finance . At this point, it is important to mention that authors from this set of clusters carry out their research mainly in Asia and were mainly formed in 2022.…”
Section: Co-authorship Analysismentioning
confidence: 99%
“…Among the most prominent of these is a group of clusters formed by Muneeza, Hassan, Beiki, Widiastuti, and Ascaray, the most relevant authors measured by published studies, as confirmed in Figure 4. The main topics addressed by this group of authors are mainly COVID‐19 and Islamic Social Finance (Hassan et al, 2021a; Hassan et al, 2021b; Herianingrum et al, 2022), the sustainability index (Widiastuti, Robani, et al, 2022), the nexus between Islamic social finance, human resources, governance, and poverty (Widiastuti, Prasetyo, et al, 2022), integration of sustainability in Islamic finance (Widiastuti, Robani, et al, 2022). At this point, it is important to mention that authors from this set of clusters carry out their research mainly in Asia and were mainly formed in 2022.…”
Section: Scientometric Analysismentioning
confidence: 99%
“…Thirdly, collaborative evaluation. By involving various institutions in the evaluation process, zakah institutions can ensure that zakah funds are utilized appropriately and in line with the designated objectives (Herianingrum et al, 2022). Furthermore, collaborative evaluation has aided zakah institutions in identifying community needs more effectively and designing more efficient programs to meet those needs (Kartini & Muarrifah, 2023).…”
Section: Collaborative Evaluationsmentioning
confidence: 99%